Cerebral embolism caused by pulmonary arteriovenous fistula: one case report - Chun-yan XU; Ying MA; Fei-qi ZHU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
DOI: 10.3969/j.issn.1672-6731.2018.12.013